2014
DOI: 10.1089/dia.2013.0192
|View full text |Cite
|
Sign up to set email alerts
|

Nonmetabolic Complications of Continuous Subcutaneous Insulin Infusion: A Patient Survey

Abstract: Background: Little is known about the frequencies and types of nonmetabolic complications occurring in type 1 diabetes patients being treated by modern insulin pump therapy (continuous subcutaneous insulin infusion [CSII]), when recorded by standardized questionnaire rather than clinical experience. Subjects and Methods: A self-report questionnaire was completed by successive subjects with type 1 diabetes attending an insulin pump clinic, and those with a duration of CSII of ‡ 6 months were selected for analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(106 citation statements)
references
References 22 publications
6
92
1
7
Order By: Relevance
“…Overall, the frequency of insulin pump adverse events has not substantially improved over the past 30 years, despite advances in technology, an observation supported by other authors [3,4]. What does appear to have changed is the severity, with reported rates in adults from the 1980s similar to those above, but of a more serious nature.…”
Section: Incidencementioning
confidence: 73%
See 3 more Smart Citations
“…Overall, the frequency of insulin pump adverse events has not substantially improved over the past 30 years, despite advances in technology, an observation supported by other authors [3,4]. What does appear to have changed is the severity, with reported rates in adults from the 1980s similar to those above, but of a more serious nature.…”
Section: Incidencementioning
confidence: 73%
“…Even higher rates have been reported more recently. Pickup et al [3] in 2014 found that 48 % of adult participants experienced pump malfunction at some point; with pump stop or no insulin delivery being the most common event recorded (in 28 % of malfunction events), while Wheeler et al [5] found that 56 % of patient-reported adverse events in children over a 12-month period (or 58 out of a total of 104 events) were due to pump malfunction, either transient or permanent. This study also suggested an association between pump malfunction and adolescence [5], but no association with age has been seen in adults [4].…”
Section: Non-metabolic Adverse Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…La complicación asociada al sitio de infusión más frecuente es la lipohipertrofia, afectando al 26% de los usuarios de ICSI 37 . La irritación y/o alergia a los adhesivos del set y la hiperpigmentación en el sitio de infusión también son frecuentes y dependen de la sensibilidad cutánea de cada paciente.…”
Section: Otros Eventos Adversos Cutáneosunclassified